Pengelolaan Program Vaksinasi Covid-19 oleh Humas Polda Provinsi Sulawesi Tengah - Fadhliah; Rizqy Alfiyaty; Kudratullah (Jurnal Administrasi Publik, 2023)
The vaccination program is one of the government's efforts to suppress the growth rate of the Covid-19 virus and control the condition of society and the country's economy. The target of people who have been vaccinated nationally has not reached the target, both from vaccines 1-2 and boosters 1-2. This is caused by the rise of hoax news so that there are still people who are afraid of being vaccinated. For this reason, education and outreach are needed through proper communication management by various sectors, one of which is the police. This study aims to determine the communication management of the Covid 19 vaccination program by Central Sulawesi Regional Police Public Relations. The method used in this research is descriptive qualitative by conducting interviews with four (4) informants and observations in the Public Relations Department. The communication management of the Covid 19 vaccination program which has been carried out by the Public Relations Division of the Central Sulawesi Provincial Police has provided sufficient information in an effort to prevent the spread of the Covid 19 virus. This process can be seen through the elements of communication management which starts with planning in the form of determining the selection of communicators, packaging messages, media selection and audience determination. The Central Sulawesi Regional Police BidHumas oversees three sub-sectors namely PID (Information and Documentation Management), Multimedia and PenMas (Public Information). At the organizing stage, these three sub-sectors coordinate with each other in disseminating information. Furthermore, the implementation is divided into actions where things that have been planned start to be carried out according to their duties and functions and communication is realized by disseminating information through media owned by the Central Sulawesi Regional Police and in collaboration with conventional mass media and online media. Finally, evaluation has not been carried out routinely so it is hoped that in the future this can be done to measure the effectiveness of messages and communication media.